Pengaruh Pengetahuan Investasi dan Motivasi Investasi Terhadap Minat Berinvestasi Mahasiswa Pendidikan Ekonomi Fakultas Ekonomi Universitas Negeri Padang - Iqtal Amhalmad1; Agus Irianto (Universitas Negeri Padang, 2019)
This study aims to determine the effect of investment knowledge and investment motivation on investment interests of students Economic Education, Economics Faculty, Padang State University. This type of research is descriptive and associative. The population of this study were 411 students from the Economics Faculty, Padang State University, 2016-1018. The sampling technique is Propositional Random Sampling with a sample of 80 students. The analysis technique used is path analysis